How can we estimate optimum fertilizer rates with accuracy and precision?. Issue 1 (2nd June 2022) - Miguez, Fernando E.; Poffenbarger, Hanna
Abstract: For decades, agronomists have invested time and resources to identify the optimum nitrogen (N) rates for cereal crops. The most common method for estimating the agronomic optimum N rate (AONR) is to design a field experiment with several N fertilizer rates and fit a regression model to the yield observations. Here, we concentrate on its accuracy and precision given choices of experimental design and statistical analysis. Our first finding is that the choice of functional form has a large agronomic effect on the estimate of the AONR, and this depends on the data‐generating model. Our second finding is that improving the precision and accuracy of AONR estimates will demand an increase in the number of N rates and replications. Finally, we propose that using either the best‐fitting model or a weighted model is preferable to always choosing either the linear‐plateau (negative bias) or quadratic‐plateau (positive bias) models. Core Ideas: Typical nitrogen response studies designs are statistically underpowered. Traditional analyses suffer from potential bias and low precision. Simulation analysis can be used for future studies to evaluate expected accuracy and precision.